2012
DOI: 10.1002/ps.3406
|View full text |Cite
|
Sign up to set email alerts
|

The story of a new insecticidal chemistry class: the diamides

Abstract: This paper describes the story of the invention of the diamides, a novel chemical class of insecticides. It starts with the pioneering work by Nihon Nohyaku researchers, who developed a herbicide lead with weak insecticidal activity to flubendiamide, a highly potent lepidoptericide. The journey continues with Nissan's isoxazolines and the invention of the anthranilamides by DuPont, culminating in the discovery of the blockbuster chlorantraniliprole and its analogue cyantraniliprole. The next steps are Syngenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(107 citation statements)
references
References 45 publications
(62 reference statements)
2
96
0
9
Order By: Relevance
“…The result with the chlorantraniliprole insecticide was as expected since this insecticide has only recently been commercialized [23][24][25] and has a highly efficient molecule since low doses of this insecticide (31.5 g a.i. ha -1 ) cause high mortality to L. coffeella; moreover, it is selective for wasps [26].…”
Section: Insecticides Resistancesupporting
confidence: 62%
“…The result with the chlorantraniliprole insecticide was as expected since this insecticide has only recently been commercialized [23][24][25] and has a highly efficient molecule since low doses of this insecticide (31.5 g a.i. ha -1 ) cause high mortality to L. coffeella; moreover, it is selective for wasps [26].…”
Section: Insecticides Resistancesupporting
confidence: 62%
“…CAP has a differential selectivity to insect receptors relative to those of mammalians of N500-fold displaying high insecticide efficacy and low toxicity to mammalian species (Cordova et al, 2006;Lahm et al, 2009;Gentz et al, 2010;Han et al, 2012;Casida and Durkin, 2013). Due to its potency and specificity, CAP is rapidly replacing other insecticides such as neonicotinoids, organophosphates, carbamates and pyrethroids for which pesticide resistance has been observed (Sattelle et al, 2008;Casida, 2009;Jeanguenat, 2013). CAP is effective against a broad range of agricultural pests in the order Lepidoptera, as well as against selected Coleoptera, Diptera and Hemiptera species (Lahm et al, 2009;Gentz et al, 2010) and its registered uses vary from agricultural crops (such as fruit trees, vegetables until cotton or rice) to ornamentals and turf grass of residential and public areas (FAO, 2007;USEPA, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Studies have shown that the active component of Ryania , ryanodine, activates the calcium channels in the sarcoplasmic reticulum of the skeletal muscle. The activated calcium channels then release an excess of calcium ions in the protein fi laments and induce skeletal muscle contraction and paralysis in insects (Bloomquist 1999 ;Jeanguenat 2013 ).…”
Section: Calcium Channelsmentioning
confidence: 99%